La preistoria del Ynglingatal - Marcello Meli (Filologia Germanica, 2024)
Vǫlundi hinum fróða THE PREHISTORY OF ‘YNGLINGATAL’. The paper aims to examine not Ynglingatal itself but rather its role in Snorri’s historiographical perspective. To this end, a description of the main genres of poetic expression among the ancient Germanic peoples will be provided, starting from the earliest reports in Tacitus. The role of ‘genealogical poetry’ in Germanic historiographical tradition will be analysed, from Jordanes to Widukind and then in Saxo and Snorri, occasionally considering also juridical texts (Leges Burgundionum). The aim of the investigation is twofold, as it purposes on the one hand to show how traditional Germanic poetry belongs to the historiography of the nonOrosian tradition, and on the other hand to document how Snorri brings to completion the slow and laborious process that had begun with Jordanes. The paper finally intends to stress the ideological value of Ynglingatal in Snorri’s historiographical programme, both as a filter from the distant past into the recent past of Harald Fair hair’s political reform and as a necessary complement to Ari Þorgilsson the Wise’s historiography